Lysosome activation clears aggregates and enhances quiescent neural stem cell activation during aging - Leeman, Dena S; Hebestreit, Katja; Ruetz, Tyson; Webb, Ashley E; McKay, Andrew; Pollina, Elizabeth A; Dulken, Ben W; Zhao, Xiaoai; Yeo, Robin W; Ho, Theodore T; Mahmoudi, Salah; Devarajan, Keerthana; et al. (Science (American Association for the Advancement of Science), 2018)
In the adult brain, the neural stem cell (NSC) pool comprises quiescent and activated populations with distinct roles. Transcriptomic analysis revealed that quiescent and activated NSCs exhibited differences in their protein homeostasis network. Whereas activated NSCs had active proteasomes, quiescent NSCs contained large lysosomes. Quiescent NSCs from young mice accumulated protein aggregates, and many of these aggregates were stored in large lysosomes. Perturbation of lysosomal activity in quiescent NSCs affected protein-aggregate accumulation and the ability of quiescent NSCs to activate. During aging, quiescent NSCs displayed defects in their lysosomes, increased accumulation of protein aggregates, and reduced ability to activate. Enhancement of the lysosome pathway in old quiescent NSCs cleared protein aggregates and ameliorated the ability of quiescent NSCs to activate, allowing them to regain a more youthful state.